TEACHERS' AWARENESS OF DISORDERS IN STUDENTS WITH EPILEPSY - Dimitrina Blagoeva; Tanya Popova (Peytchinski Publishing, 2022)
Epilepsy is one of the most common neurological diseases, characterized by recurrent epileptic seizures. Epilepsy can be caused by various factors affecting the brain. Any process affecting the child's brain during its formation leads to insufficient maturation of nerve elements in their morpho-functional structure. Depending on the degree and nature of the brain damage, the location of the lesion, its depth and spread, there are different forms of epilepsy, manifesting themselves in different ways. Disorders accompanying the disease are: attention deficit, neuropsychiatric disorders, motility disorders. Children with epilepsy may have a general intellectual disability (mental retardation), global developmental delay, hearing or vision impairment, autism spectrum disorders and others. The aim of the present study is to research and analyze the awareness of teachers working in educational institutions about the disorders and the presence of learning difficulties in students with epilepsy. The materials and methods used in the study are sociological, documentary and graphical analyses of the results. The study included 133 teachers working in schools in the city of Sofia. Results and discussion: The study found that the largest group of teachers aged 31 to 40 years - 39.10%. About 57% of respondents said that students with epilepsy have an attention deficit, but a large percentage of respondents said that there was a decrease in concentration. The study found that teachers were aware of the disease but did not have enough information about the disorders that accompany epilepsy and the learning difficulties that students with epilepsy may have.